2008
DOI: 10.1123/jpah.5.1.117
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Perceived and Objectively Measured Crime With Physical Activity: A Cross-Sectional Analysis

Abstract: Background-Crime is one aspect of the environment that can act as a barrier to physical activity. The goals of this study were to (1) compare measures of perceived crime with observed crime and (2) examine the association between the independent and combined effects of objective and perceived crime on physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
5
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 23 publications
(28 reference statements)
12
82
5
3
Order By: Relevance
“…It was defi ned as locations people could reach within ten minutes walking A modifi ed scale, based on the NEWS version validated in Brazil, was used to establish data validity and the true relationship with the contextual data of the environment. 14 Although the contextual indicators are associated and follow the same direction of relationship as indicators previously found to be related to physical activity, 17 a recent study found low agreement between objectively measured data and self-reported data. 1 Therefore, it is possible that the objective and perceived variables capture different aspects of the environment, which would explain the low agreement.…”
Section: Discussionmentioning
confidence: 73%
“…It was defi ned as locations people could reach within ten minutes walking A modifi ed scale, based on the NEWS version validated in Brazil, was used to establish data validity and the true relationship with the contextual data of the environment. 14 Although the contextual indicators are associated and follow the same direction of relationship as indicators previously found to be related to physical activity, 17 a recent study found low agreement between objectively measured data and self-reported data. 1 Therefore, it is possible that the objective and perceived variables capture different aspects of the environment, which would explain the low agreement.…”
Section: Discussionmentioning
confidence: 73%
“…Using official crime statistics however has limitations with evidence of underreporting of crime in minority and lower income neighborhoods. 80 Finally, our sample was drawn from urban areas and therefore our findings may not apply to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, a similar chasm exists when perceived and actual safety from crime have been examined (McGinn et al, 2008;Hoehner et al, 2005, andKirtland et al, 2003) and in describing perceived and objective built environment characteristics like density, walkability, and land use mix around one's home (Moudon et al, 2005;McGinn et al, 2007McGinn et al, , 2008Kirtland et al, 2003).…”
Section: Prior Evidence and Conceptual Frameworkmentioning
confidence: 97%